Lightweight reduced graphene oxide-ZnO nanocomposite for enhanced dielectric loss and excellent electromagnetic interference shielding. (1st September 2019) - Singh, Ashwani Kumar; Kumar, Ajit; Srivastava, Amit; Yadav, Amar Nath; Haldar, Kamal; Gupta, Vinay; Singh, Kedar
Abstract: In this paper, authors report a facile synthesis of reduced graphene oxide-ZnO (rGO-ZnO) nanocomposite via the solvothermal method for excellent electromagnetic interference (EMI) shielding application. Various characterization tools such as Transmission Electron Microscope (TEM), X-ray diffractometer (XRD) and Raman spectroscope have been employed to understand the morphology and crystal structure of rGO-ZnO nanocomposite, which clearly reveals ZnO nanoparticles (with average size ∼25 nm) to get dispersed well over the surface of rGO. These ZnO nanoparticles, assembled over the top of rGO sheets, form an rGO-ZnO heterostructure with enhanced polarization centers. ZnO nanostructures not only prevent rGO nanosheets to agglomerate but also to contribute significantly in improved scattering, dielectric loss, and impedance matching properties of heterostructure nanocomposite. EMI shielding properties of rGO-ZnO nanocomposites have been evaluated in X-band frequency range (8–12 GHz) and indicate clearly that rGO-ZnO (SET ∼ 38 dB) nanocomposite exhibits an excellent shielding property as compared to its constituent components (SET ∼ 22 dB for rGO and ∼4 dB for ZnO nanoparticles, respectively). Variation of real and imaginary parts of permittivity and permeability provides the idea of attenuating rGO-ZnO nanocomposite. Moreover, it's dielectric and magnetic loss parameters demonstrate the impedance matching characteristics of the rGO-ZnO nanocomposite. Graphical abstract: Image 1